Prosthodontic Rehabilitation of a Kennedy’s Class I Edentulous Arch: Integration of Altered Cast Technique and CAD-Assisted Cast Partial Denture Fabrication: A CASE REPORT - Gupta, DR. Vaishali Gupta, DR. Sumit Singh Phukela, DR. Bhupender Yadav, DR. Harshita Goyal, DR. Shweta Jaglan, Daksh Sethi (Journal of Neonatal Surgery, 2025)
The rehabilitation of Kennedy’s Class I partially edentulous cases presents unique biomechanical challenges due to the combined reliance on tooth and tissue support. Cast partial dentures (CPDs) offer a viable alternative to implant-supported prostheses, particularly when implants are contraindicated due to systemic, anatomical, or financial limitations. This case report highlights the prosthodontic management of a patient with a completely edentulous maxillary arch and a partially edentulous mandibular arch (Kennedy’s Class I, modification 1) using a combination of an anterior fixed partial denture (FPD) and a posterior CPD fabricated through computer-aided design (CAD) technology. The altered cast impression technique was employed to enhance the fit, stability, and functional adaptation of the CPD by accurately recording the edentulous ridge under functional conditions. Additionally, CAD-assisted framework fabrication ensured precision, improved adaptation, and optimized stress distribution. The final prosthesis successfully restored masticatory function, comfort, and patient satisfaction. This case underscores the significance of combining conventional prosthodontic principles with digital advancements to improve the predictability and efficiency of removable prosthesis fabrication.